Suppressor of cytokine signaling 3 (SOCS3) is related to pro-inflammatory cytokine production and triglyceride deposition in turbot (Scophthalmus maximus). Issue 70 (November 2017) - Tan, Peng; Peng, Mo; Liu, Dongwu; Guo, Huarong; Mai, Kangsen; Nian, Rui; Macq, Benoit; Ai, Qinghui
Abstract: Turbot ( Scophthalmus maximus ) is an economically important fish that is farmed by aquaculture for human consumption. Aquacultured turbot are commonly fed a high-lipid diet; however, this diet causes excessive lipid deposition and the overexpression of pro-inflammatory cytokines. Studies in mammals have indicated that a relationship exists between pro-inflammatory cytokine overexpression and altered lipid metabolism through the activation of suppressor of cytokine signaling 3 (SOCS3). In this study, we investigated the relationship between SOCS3 and triglyceride (TG) deposition and mechanism of SOCS3 activation in farmed turbot fed high-lipid diet (HLD). TG content increased with SOCS3 production, mediated by toll-like receptor-nuclear transcription factor kappa-B (TLR-NFκB) signaling in the liver of turbot fed a HLD and in turbot primary liver cells incubated with oleic acid (OA). Overexpression of SOCS3 increased TG deposition via the increased production of mature sterol regulatory element binding protein 1 ( m -SREBP-1). Knockdown of SOCS3 in turbot primary liver cells resulted in normalized TG deposition and decreased m -SREBP-1 production. These results suggest that the HLD and OA can induce cytokine expression by activating the TLR-NFκB signaling pathways, resulting in increased SOCS3 expression. It is proposed that SOCS3 enhances m -SREBP-1 production, leading to TG deposition. These findings provide important new insights into the relationship between cytokine expression and TG deposition and mechanism of HLD-induced pro-inflammatory response, which could help to improve the health of farmed turbot and a better understanding of fish immunity. Graphical abstract: Highlights: HLD and OA activate the TLR-NFκB signaling pathway, resulting in cytokines expression. NFκB dependent SOCS3 production could be induced by TNFα. Overexpression of SOCS3 increased TG deposition via the increased production of m -SREBP-1. Knockdown of SOCS3 resulted in decreased TG deposition and m -SREBP-1 production.